The association between glycaemic control during hospitalization and risk of adverse events: A retrospective cohort study. Issue 3 (27th May 2021) - Deng, Lan; Aibibula, Wusiman; Talat, Zahra; Filion, Kristian B.; Eintracht, Shaun; Dasgupta, Kaberi; Tagalakis, Vicky; Majdan, Agnieszka; Yu, Oriana Hoi Yun
Abstract: Introduction: Hyperglycaemia is common during hospitalization; glycaemic targets in non‐critical care settings have not been well studied. We assessed associations between inpatient glycaemic control and adverse events. Methods: We conducted a retrospective cohort study on non‐critically ill medical patients hospitalized in a tertiary care hospital between 2015 and 2018. Mean glycaemia during the first four days of hospitalization was categorized as 4.0–7.0 mmol/L, 7.1–10.0 mmol/L and >10.0 mmol/L. The primary outcome was a composite of adverse events including mortality, infections, acute kidney injury, thromboembolic and cardiovascular events. The secondary outcome was hypoglycaemia, defined as any glycaemia <4.0 mmol/L. Logistic regression was used to assess adverse events, and a Cox proportional hazards model was used to estimate hypoglycaemia risk. Results: Our cohort included 1, 368 patients, of whom 407 (29.8%) experienced an adverse event. We did not find associations between glycaemia of 4.0–7.0 mmol/L (adjusted odds ratio [OR]: 0.88, 95% confidence interval [CI]: 0.63–1.23) or glycaemia of >10.0 mmol/L (adjusted OR: 0.98, 95% CI: 0.75–1.28) and the occurrence of adverse events, compared to a glycaemia of 7.1–10.0 mmol/L. Glycaemia of >10.0 mmol/L was associated with an increased risk of hypoglycaemia (adjusted hazard ratio [HR]: 1.72, 95% CI: 1.21–2.45). Hypoglycaemia was associated with adverse events (adjusted OR 1.85, 95% CI 1.31–2.60). Conclusions: Neither glycaemia of 4.0–7.0 mmol/L nor glycaemia of >10.0mmol/L during non‐critical care hospitalization was associated with increased adverse events. Glycaemia of >10.0 mmol/L was associated with increased hypoglycaemia, likely due to aggressive glucose lowering. These findings highlight the need for further studies to discern optimal inpatient glycaemic targets. Abstract : Few studies have assessed the association between various glycaemic targets and adverse outcomes during hospitalization. Our study assessed whether glycaemia levels (ie 4.0–7.0 mmol/L, 7.1–10.0 mmol/L and >10 mmol/L) during early hospitalization is associated with an increased risk of adverse events and hypoglycaemia. Our results showed that the glycaemic targets defined in our study were not associated with an increased risk of adverse events during hospitalization; however, hypoglycaemia (ie <4.0 mmol/L) was associated with an increased risk of adverse events during hospitalization.